Radically Different-A Themed Issue in Honor of Professor Bernd Giese on the Occasion of His 80th Birthday - Fromm, Katharina M. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Issue came together thanks to contributions from friends and colleagues of Prof. Bernd Giese on behalf of his 80th birthday on 2 June 2020. Reflecting on the varied interests of Bernd in all areas of chemistry, this issue contains work, including historical work, on inorganic coordination chemistry, nanomaterials, theory, and organic and radical chemistry-Bernd's core expertise. It is wonderful that so many different publications came together from all over the world, as both review articles and original contributions, making this Special Issue worthwhile reading.